New Approaches to Teaching Critical Thinking Skills through a New EFL Curriculum - Itmeizeh, Mahmoud; Hassan, Ahdi (International Journal of Psychosocial Rehabilitation, 2020)
This study aims at investigating new approaches to teaching critical thinking skills through a new EFL curriculum for Palestinian EFL learners. The ultimate aim of the study hopes to provide the Palestinian teachers, students, policymakers and curricula designers some guidelines for integrating critical thinking skills into EFL curricula. To develop a comprehensive understanding of the phenomena, qualitative and quantitative methods were used. This mixed approach is used to assure validity depending on different data collection sources. The researcher used a 32-item questionnaire adapted from (Saeed et al., 2012 & Rezaei et al., 2011) that addresses EFL teachers. The content analysis method was also used through which 79 English language supervisors' reports were systematically analyzed. The findings of the study showed that most of their EFL students do not recognize critical thinking skills. Analysis of the reports showed that most periods delivered to EFL students don not enhance critical thinking skills. Based on the results of the questionnaire and the content analysis of the report, the researcher presented some activities, guidelines, and strategies to be utilized by EFL teachers regarding course content, methods of teaching, classroom management, and EFL students' assessment.